Decoronation: An Alternative Treatment for Replacement Root Resorption - Marianne Sala; Asunción Mendoza-Mendoza; Rosa-María (Hindawi Limited, 2017)
Introduction. Ankylosis and disrupted or altered root development are frequent complications associated with intrusive luxation and tooth avulsion lesions. Various forms of treatment have been described according to the severity of the trauma and root development. The literature shows that decoronation is an ideal treatment in cases where replacement resorption occurs. Methods. Two clinical cases are presented: involving intrusive luxation [15-year-old female patient with an affected maxillary left lateral incisor (2.2)] and a replanted avulsed tooth [8-year-old male patient with avulsion of the right maxillary central incisor (1.1)]; both cases presented advanced root resorption so that decoronation with a prosthetic tooth replacement was decided as the final treatment option. Results. In the short-term follow-up, patients were asymptomatic and had no functional problems. Radiographs showed that crestal bone height had been preserved. Conclusions. Preserving the decoronated root in the alveolar process not only helps to maintain bone volume but also enables vertical bone growth and facilitates the future insertion of an implant.